EPD Congress 2016 - Allanore, Antoine; Bartlett, Laura; Wang, Cong.; Zhang, Lifeng; Lee, Jonghyun; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
EPD Congress is an annual collection that addresses extraction and processing metallurgy. The papers in this book are drawn from symposia held at the 2016 Annual Meeting of The Minerals, Metals & Materials Society. The 2016 edition includes papers from the following symposia: •Materials Processing Fundamentals •Advanced Characterization Techniques for Quantifying and Modeling Deformation.
Keywords: Metals; Materials; Mechanical engineering; Metals and Alloys; Materials Engineering; Mechanical Engineering